SCIENTOMETRIC ANALYSIS ON UTILIZATION OF AGRICULTURAL WASTE FOR BOARD AND PANEL PREPARATION - SHARMA, PRERNA; PRASATH KUMAR, Dr.V.R (PREPARE@u® | IEI Conferences, 2021)
Agricultural wastes are widely distributed in the environment, creating a health and environmental risk. Because of their environmental and health benefits, natural insulating materials are becoming increasingly popular. The goal of this research is to provide a precise method for measuring science and technology development trends in agricultural waste panel and board production, with sustainability as the most important factor. The papers were gathered using a bibliographic approach based on the Scopus database. Using scientometric analysis, researchers can look at the trends in these articles, including keywords, journals, countries, and authors. The use of waste in energy-efficient architecture is an emerging research topic. The filter is applied based on the paper’s keyword of panel and board, and the observed properties are detailed in the study. The research is being carried out to gain a practical understanding of the various materials that have been used in the preparation of boards and panels, as well as the tests that will be carried out, such as modulus of rupture, elasticity, thermal conductivity, energy analysis, small hot box test, and life cycle assessment to assess energy usage and CO2 emissions. The future scope has also been added in the conclusion.